An unpredictable Gospel: American evangelicals and world Christianity, 1812-1920 - Case, Jay Riley (Oxford University Press, 2012)
Jay Case examines the efforts of American evangelical missionaries, arguing that if they were agents of imperialism they were poor ones. Western missionaries had a dismal record of converting non-Westerners to Christianity.